Cervical Vagal Schwannoma: A Case Report and Literature Review - Sunil Thatal; Susmin Karki; Asmita Parajuli; Yamuna Agrawal; Deepak Paudel (Clinical Case Reports)
ABSTRACT Vagal schwannoma is a benign tumor that can occasionally develop into malignant degeneration from the Schwann cells surrounding the cranial, peripheral, and autonomic nerves. The schwannomas arising in the head and neck region are rare, and rarer is their origin from the cervical vagus nerve. Despite being challenging, multiple treatment options are available, including observation, complete tumor excision with nerve transaction, and nerve preservation, depending on clinicoradiological factors. The cervical vagal schwannoma is a rare entity. We report a rare case of a 50‐year‐old female with painless swelling on the right side of the neck associated with mild discomfort during swallowing, diagnosed as cervical vagal schwannoma.